THE RELATIONSHIP BETWEEN THE EMOTIONAL LABOR AND BURNOUT LEVELS OF EFL TEACHERS AT UNIVERSITY PREPARATORY SCHOOLS - Ergül Bayram, Pınar; Eveyik-Aydın, Evrim (TEFLIN Journal, 2023)
This study investigated the relationship between the emotional labor and burnout levels of English as a Foreign Language (EFL) teachers in languagepreparatory schools at Turkish universities. Data were collected from 179 EFL teachers from both state and foundation universities, using Turkish adaptations of the Emotional Labor Scale covering surface acting,deep acting andnaturally felt emotions, andthe Maslach Burnout Inventory Educators Survey including emotional exhaustion, depersonalization, and reduced personal accomplishment.Thefindings revealed that the most commonly experienced dimensions of emotional labor and burnout were naturallyfelt emotions and emotional exhaustion, respectively.Surface acting showed a positive correlation withemotional exhaustion and depersonalization, whereas displaying genuine emotions had a negative correlation with burnout.Furthermore, surface acting and naturally felt emotions emerged assignificant predictors of emotional exhaustion and depersonalization, while displaying natural emotions was a significant predictor of reduced personal accomplishment. These findings suggest that masking emotions fosters exhaustion and alienation from students,while the display of internalized and genuine emotionsincreases the sense of personal accomplishment and alleviates burnout. Therefore, we suggestthat institutions and administrators should support the emotional well-being of EFL teachersby encouraging their display of preferred feelings instead of imposing display rules on them.